MEMAHAMI INTERIOR SEBAGAI PENGHUBUNG - Diana Thamrin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2016)
Title: Understanding Interior as a Connector Interior design is a discipline that is very close to the complexities and the needs of human life. However, the intepretation and practice of interior design are often limited to decoration and contents within the physical boundaries of architecture. This paper aims to provide another perspective regarding the concept of interior that is, as a significant connector between humans and their living environment along with architecture, so that the methods and practice of interior design as well as architecture may expand more than what has been observed today. The paper is a result of a qualitative research through literature review and exploration of case studies. Results conclude to several interior and architectural design techniques based on the perception of interior as a ?connector? that could be used, such as the blurring of physical boundaries, programmatic manipulation, innovation of material continuity and configuration of architectural elements into interior elements. Through the physical as well as conceptual manipulation of space, the intepretation of interior design would no longer be limited to the contents within the physical boundaries of architecture but rather a truly important connector along with architecture, between humans and their living environment.